Soil temperature effects on the structure and diversity of plant and invertebrate communities in a natural warming experiment - Robinson, Sinikka I.; McLaughlin, Órla B.; Marteinsdóttir, Bryndís; O'Gorman, Eoin J. (The Journal of animal ecology, 2018)
1. Global warming is predicted to significantly alter species physiology, biotic interactions and thus ecosystem functioning, as a consequence of coexisting species exhibiting a wide range of thermal sensitivities. There is, however, a dearth of research examining warming impacts on natural communities. 2. Here, we used a natural warming experiment in Iceland to investigate the changes in above-ground terrestrial plant and invertebrate communities along a soil temperature gradient (10°C-30°C). 3. The α-diversity of plants and invertebrates decreased with increasing soil temperature, driven by decreasing plant species richness and increasing dominance of certain invertebrate species in warmer habitats. There was also greater species turnover in both plant and invertebrate communities with increasing pairwise percentage cover of vegetation at the community level, driven by contrasting effects at the population level. 4. There was a reduction in the mean body mass and an increase in the total abundance of the invertebrate community, resulting in no overall change in community biomass. There were contrasting effects of temperature on the population abundance of various invertebrate species, which could be explained by differential termal tolerances and metabolic requirements, or may have been mediated by changes in plant community composition. 5. Our study provides an important beseline from which the effect of changing environmental conditions on terrestrial communities can be tracked. It also contributes to out understanding of why community-level studies of warming impacts are imperative if we are to disentangle the contrasting thermal responses of individual populations.